2017
DOI: 10.1371/journal.pone.0187426
|View full text |Cite
|
Sign up to set email alerts
|

A causal mediation model of ischemia reperfusion injury in the retina

Abstract: The goal of this study is to develop a model that explains the relationship between microRNAs, transcription factors, and their co-target genes. This relationship was previously reported in gene regulatory loops associated with 24 hour (24h) and 7 day (7d) time periods following ischemia-reperfusion injury in a rat’s retina. Using a model system of retinal ischemia-reperfusion injury, we propose that microRNAs first influence transcription factors, which in turn act as mediators to influence transcription of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
2
0
Order By: Relevance
“…The sec1 family domain (SCFD2) gene, identified in the older group, is a protein-coding gene that participates in protein transport and exocytosis [ 40 ] and is involved in multiple personality disorders. In terms of its potential role in ophthalmic diseases, a previous study has found the opposite effect of the Scfd2 gene on STAT1 and miR-493 regulators, which are associated with ischemia, a type of common pathological pathway for neuronal cell degeneration associated with many retinal diseases [ 41 , 42 ]. Other results from GWAS analysis also indicated that several variants within the SCFD2 gene locus achieved genome-wide statistical significance in their association with cataracts in the Australian Shepherd breed of domestic dogs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sec1 family domain (SCFD2) gene, identified in the older group, is a protein-coding gene that participates in protein transport and exocytosis [ 40 ] and is involved in multiple personality disorders. In terms of its potential role in ophthalmic diseases, a previous study has found the opposite effect of the Scfd2 gene on STAT1 and miR-493 regulators, which are associated with ischemia, a type of common pathological pathway for neuronal cell degeneration associated with many retinal diseases [ 41 , 42 ]. Other results from GWAS analysis also indicated that several variants within the SCFD2 gene locus achieved genome-wide statistical significance in their association with cataracts in the Australian Shepherd breed of domestic dogs [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining the viability of the donor eye post-enucleation stands as a paramount challenge in whole-eye transplantation, underpinned by three critical parameters: The recovery of visual function post-transplant, the resilience of the outer retina to ischemia, and the survival of RGCs[ 33 , 82 , 83 ]. The journey toward understanding and optimizing these factors reveals a complex interplay of biological and technical considerations.…”
Section: Limits To Successmentioning
confidence: 99%